PENGGUNAAN METODOLOGI SCRUM DENGAN PENDEKATAN GOAL-ORIENTED REQUIREMENT ENGINEERING DALAM PENGEMBANG SISTEM INFORMASI KESEHATAN - Trinanda, Muhammad Satria Putra; Irawati, Irawati; Hasnawi, Mardiyyah (NERO (Networking Engineering Research Operation), 2024)
The information obtained by the public is inadequate, and sometimes they still really need complete information, one of which is about diseases. The provision of media information must be proven accurate and should not be reported by organizations that do not have authority. In this case, health foundations have the right to provide information that is trusted for its authenticity, especially in providing information data regarding tuberculosis disease. The purpose of this research is to develop a tuberculosis tuberculosis information system on the Yamali TB platform with the Goal-Oriented Requirement Engineering (GORE) approach and the Scrum method. Information system development is carried out through several main activities, namely Problem Identification, Problem Analysis, Goal Identification, Backlog Prioritization, System Design, Initial Discussion, Program Design and Final Evaluation using the System Usability Scale assessment method. The results showed that the level of user satisfaction with the information system based on the usability test obtained an average of 77 and was ranked at Grade Scale C, Acceptability Ranges at the Acceptable level, and Adjective Ratings at the Good level which means that the information system developed is well received by users.Keywords: Goal-Oriented Requirement Engineering, Grade Scale, Scrum, System Usability Scale.